Corrosion monitoring of rock bolt by using a low coherent fiber-optic interferometry. (April 2015) - Wei, Heming; Zhao, Xuefeng; Li, Dongsheng; Zhang, Pinglei; Sun, Changsen
Abstract: Corrosion of rock bolts is a major cause for deterioration of the anchor-reinforced concrete slopes structures. In order to evaluate this corrosion-based deterioration in an early stage, a nondestructive technique was required. However, until now, there are no commercialized solutions that are straightforwardly available. Here, a low-coherent fiber-optic sensing technique was developed. This method can carry out the monitoring of the corrosion-caused expansion at the accuracy of sub-microstrains by circled the sensing optical fiber in two ways. One was wound the fiber on the surface of steel rock bolt directly, and thereby generated a nonuniformity in the interface of cement with rock bolt. The other was circled the fiber on a cement mortar cushion without destroying the interface any way. The sensing fiber was configured as one arm of the fiber-optic Michelson interferometer. The acceleration corrosion experiments demonstrated that a uniform interface between cement and rock bolt determined the progress of corrosion development. An early stage evaluation of the corrosion development in rock bolts was monitored. Highlights: The effectiveness of fiber optic sensors for corrosion evaluation was verified. A uniform interface of rock bolt with cement determined corrosion development. Non-destruction of fiber optic sensor was critical for corrosion monitoring.